Strengthening the Role of Teachers as Agents of Regional Language Preservation through Family Literacy Learning Strategies - Stella Talitha; Yeti Mulyati; Khaerudin Kurniawan; Dadang S. Anshori; Vismaia S. Damaianti (LPPM Universitas PGRI Sumatera Barat, 2024)
This study investigates how multimodal learning practices can cultivate critical and ethical information and digital literacy among university students in teacher education. Responding to growing concerns about superficial digital skills and limited attention to ethics, the research explores how a multimodal writing and digital literacy course supported students’ development beyond technical proficiency. A qualitative interpretive case study was conducted in an Indonesian university, involving one lecturer and twelve undergraduate students over a twelve-week semester. Data were generated through non-participant classroom observations, semi-structured individual and group interviews, students’ reflective journals, and multimodal artefacts such as infographics, digital essays, and video projects, and were analyzed using thematic analysis. Findings reveal three interconnected processes. First, students developed critical awareness as they interrogated source credibility, questioned visual and verbal representations, and recognized how semiotic choices shape meaning. Second, ethical reflection emerged when students engaged with issues of attribution, authorship, representation, and audience impact, gradually internalizing fairness, respect, and responsibility as part of their digital identities. Third, collaborative multimodal projects transformed learning into a shared ethical practice, fostering dialogic negotiation, empathy, and intercultural awareness. The study concludes that intentionally scaffolded multimodal pedagogy can reframe digital literacy as a social, cultural, and moral practice, offering concrete design and assessment principles for preparing reflective, responsible digital citizens in higher education.